Legal and systemic implications of the 2023 Polish act on certain medical professions–regulation, workforce requirements, healthcare system impact - Pacian, Jolanta Agnieszka; Piekut, Marlena Jolanta (Frontiers in Public Health, 2025)
BackgroundIn August 2023, Poland enacted the Act on Certain Medical Professions, introducing binding legal requirements for 15 previously unregulated health professions. The Act mandates continuous professional development (CPD) and registration in the Central Register of Persons Authorized to Practice a Medical Profession. Its primary aim is to enhance legal accountability, standardize qualifications, and improve healthcare quality and safety.ObjectiveThe aim of this article is to provide a comprehensive assessment of the 2023 Act on Certain Medical Professions, including an analysis of the effectiveness of its legal provisions in strengthening professional accountability and patient safety, as well as an evaluation of its potential economic implications for the healthcare system.MethodsEmploying a normative-descriptive approach, the study conducts a legal and policy analysis and includes a comparative overview of similar regulatory models in selected EU countries.ResultsThe Act formalizes these professions and introduces significant legal and organizational duties. While it may result in short-term costs—such as those related to ICT systems, registration, and CPD—it offers long-term benefits through improved care quality, reduced medical errors, and enhanced patient trust.ConclusionThe Act marks a major reform in Polish healthcare regulation. Despite higher compliance demands, it strengthens professional standards and system efficiency. Future empirical studies should examine its long-term impact.